Impacting governance and reaching rural women through experience capitalization - Choudhury, Mahua Roy (Technical Centre for Agricultural and Rural Cooperation, 2019)
The adoption of experience capitalization by the Bihar Rural Livelihoods Promotion Society (JEEViKA) in India has helped us disseminate the organisation's learnings and reach a wider, more diverse audience. This has resulted in the widespread adoption of the practices JEEViKA promotes for the development of agriculture, livestock rearing and health and nutrition.